De Verdwenen Opera van Antwerpen: Het Theater van het Tapissierspland, 1711-1829 - De Paepe, Timothy 1981-; Museum Vleeshuis | Klank van de Stad (Antwerp, Belgium) (Antwerp BAI, 2022)
In October 1711, the Tapissierspand Theatre opened its doors. It was Antwerp's first major theatre. For more than a century, the people of Antwerp could go there for balls, concerts, theatre and, above all, opera. Countless fascinating actors, actresses and musicians once performed there. The theatre was the main venue for important receptions, until the Tapissiers' Theatre had to make way for the Bourlaschouwburg in 1829. This cahier takes the reader to Antwerp's vanished opera house. (Translated with DeepL.com)
Keywords: 18th Century (1701-1800); 19th Century (1801-1900); Theater history; Opera; Antwerp (Belgium)